2021
DOI: 10.1111/all.14986
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ tissue‐resident memory T cells recruit neutrophils that are essential for flare‐ups in contact dermatitis

Abstract: Background: Allergic contact dermatitis (ACD) is classically described as a delayedtype hypersensitivity reaction. However, patients often experience flare-ups characterized by itching erythema, edema, and often vesicles occurring within hours after re-exposure of previously sensitized skin to the specific contact allergen. Recent studies have indicated that skin-resident memory T (T RM ) cells play a central role in ACD.However, the pathogenic role of T RM cells in allergen-induced flare-ups is not known.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 44 publications
6
50
0
1
Order By: Relevance
“…4C). It was recently shown that CD8 + T RM cells mediated neutrophil recruitment by inducing CXCL1 and CXCL2 production in the skin (Funch et al, 2022). We found that Ifngr2 , encoding the IFN-γ receptor 2, was preferentially expressed by the stromal and myeloid compartment, which also expressed the transcripts Cxcl1 , Cxcl2 and Cxcl3 , reported as neutrophil-attracting chemokines (Dilulio et al, 1999; Engeman et al, 2004; Kish et al, 2012) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4C). It was recently shown that CD8 + T RM cells mediated neutrophil recruitment by inducing CXCL1 and CXCL2 production in the skin (Funch et al, 2022). We found that Ifngr2 , encoding the IFN-γ receptor 2, was preferentially expressed by the stromal and myeloid compartment, which also expressed the transcripts Cxcl1 , Cxcl2 and Cxcl3 , reported as neutrophil-attracting chemokines (Dilulio et al, 1999; Engeman et al, 2004; Kish et al, 2012) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, mounting evidence has shown that type 1 innate lymphoid cells, including natural killer (NK) cells and ILC1s, can also mediate a recall reaction in the animal model of ACD, hapten-induced contact hypersensitivity (CHS) (O’Leary et al, 2006; Sun et al, 2009; Paust et al, 2010; Peng et al, 2013; Majewska-Szczepanik et al, 2013; Wang et al, 2018; Wight et al, 2018). The recurrence and severity of ACD and CHS have been attributed to the accumulation and reactivation of resident memory CD8 + T (T RM ) cells at the sites of hapten exposure (Gaide et al, 2015; Schmidt et al, 2017; Gamradt et al, 2019; Funch et al, 2022). Although effector mechanisms driving inflammation have been extensively studied, regulatory mechanisms that cease the response and determine the kinetics of its resolution are not sufficiently understood.…”
Section: Introductionmentioning
confidence: 99%
“…IL-17 is produced by γδ T cells in the skin during the process 18 . During elicitation, CD8 + tissue-resident memory T www.nature.com/scientificreports/ cells trigger a massive neutrophil infiltration in the epidermis within 12 h of re-exposure to contact allergens 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the area is not the typical location of the ROAT, it was close to the patch test areas where aluminium‐specific T cells could induce a response. Additionally, a recent mouse study showed that upon exposure of naïve skin to the allergen in question, inflammation was mediated by circulating T cells 48‐96 hours following exposure 37 …”
Section: Discussionmentioning
confidence: 99%